Differential expression of the aryl hydrocarbon receptor pathway associates with craniofacial polymorphism in sympatric Arctic charr - Ahi, Ehsan; Steinhäuser, Sophie; Pálsson, Arnar; Sigrídur Franzdóttir; Sigurdur Snorrason; Maier, Valerie; Jónsson, Zophonías (Figshare, 2015)
Abstract Background The developmental basis of craniofacial morphology hinges on interactions of numerous signalling systems. Extensive craniofacial variation in the polymorphic Arctic charr, a member of the salmonid family, from Lake Thingvallavatn (Iceland), offers opportunities to find and study such signalling pathways and their key regulators, thereby shedding light on the developmental pathways, and the genetics of trophic divergence. Results To identify genes involved in the craniofacial differences between benthic and limnetic Arctic charr, we used transcriptome data from different morphs, spanning early development, together with data on craniofacial expression patterns and skeletogenesis in model vertebrate species. Out of 20 genes identified, 7 showed lower gene expression in benthic than in limnetic charr morphs. We had previously identified a conserved gene network involved in extracellular matrix (ECM) organization and skeletogenesis, showing higher expression in developing craniofacial elements of benthic than in limnetic Arctic charr morphs. The present study adds a second set of genes constituting an expanded gene network with strong, benthic–limnetic differential expression. To identify putative upstream regulators, we performed knowledge-based motif enrichment analyses on the regulatory sequences of the identified genes which yielded potential binding sites for a set of known transcription factors (TFs). Of the 8 TFs that we examined using qPCR, two (Ahr2b and Ap2) were found to be differentially expressed between benthic and limnetic charr. Expression analysis of several known AhR targets indicated higher activity of the AhR pathway during craniofacial development in benthic charr morphotypes. Conclusion These results suggest a key role of the aryl hydrocarbon receptor (AhR) pathway in the observed craniofacial differences between distinct charr morphotypes.